DNase I sensitivity of the alpha 2(I) collagen gene: correlation with its expression but not with its methylation pattern. - McKeon, C (1984)
The chromatin structure of the chick alpha 2(I) collagen gene was probed with DNase I. Because our previous work strongly suggested that the 5' end of this gene is not methylated whereas the rest of the gene is methylated whether or not the gene is expressed, we compared the relative DNase I sensitivity of the methylated and unmethylated segments. Both regions demonstrate similar relative DNase I sensitivities within a given tissue. In chromatin of chick embryo fibroblasts, we find a DNase I hypersensitive site which maps between 100 and 300 bp preceding the start of transcription. This site is not found in brain chromatin but is present in chick embryo fibroblasts transformed by Rous Sarcoma virus although the rate of transcription of the alpha 2(I) collagen gene is greatly reduced in these cells. Hence, the mechanism responsible for the large decrease in alpha 2(I) collagen gene expression in RSV transformed cells is different from the mechanism that is responsible for the presence of a DNase I hypersensitive site in the promoter. Furthermore, changes in the DNase I sensitivity of the chromatin of the alpha 2(I) collagen promoter occur without changes in the methylation pattern of the gene.